Pertumbuhan Tiga Kultivar Padi (Oryza sativa L.) Terhadap Aplikasi Pupuk Bio Cair dan Kondisi Tanah Pertanian Pasca Erupsi Merapi 2010 - Umi Siswanti, Dwi; Rachmawati, Diah (Biogenesis, 2013)
The eruption of Mount Merapi at the end of 2010, which resulted in the destruction of land and crops are changing wetland into dry land. Sleman which is located south of Mount Merapi became one of the areas that most affected by the eruption of Merapi in 2010. It is necessary to improve the processing of soil physical properties of degraded areas and efforts to restore agricultural soil nutrient. Returning soil nutrients can be cultivated with the addition of organic material or the addition of microbes. The research aims to analyze the growth of three cultivars of rice (Oryza sativa L.) againstthe application of biofertilizer in paddy fields were affected by the eruption of Merapi in 2010. These three rice cultivars are Situbagendit, Inpari 20 and Ciherang. This research was conducted by applying the biofertilizer as much as 10 liters / ha were given three times during the vegetative phase, ie: 7, 21and 35 days after planting. The results of this research indicate that the three rice varieties ie: Situbagendit, Ciherang and Inpari 20 have an optimal growth and an increase in soil nutient content in biofertilizer application.Keywords: biofertilizer, degraded land, Merapi eruption, rice